1976
DOI: 10.1073/pnas.73.10.3333
|View full text |Cite
|
Sign up to set email alerts
|

Nature of O2 and CO binding to metalloporphyrins and heme proteins.

Abstract: The O2 vibration of dioxygen adducts of Fe and Co model complexes of a,a,ac,a-tetrapivalamidophenylporphyrin ("picket fence" porphyrin, TpivPP) with 1-methylimidazole and 1-tritylimidazole as axial bases are reported, obtained with difference techniques between 1'602,O180, 160-.80 A continuing controversy exists over the nature of ligand bonding to hemoproteins and metalloporphyrins. While it has been well established that both iron and cobalt bind dioxygen in a bent end-on fashion (1, 2), physical measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
262
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(270 citation statements)
references
References 43 publications
(24 reference statements)
7
262
0
1
Order By: Relevance
“…Of the other two common Fe(II) ligands, CO and NO, NO is the best molecular mimic for O 2 binding. Both O 2 and NO prefer a bent geometry, whereas CO prefers a linear geometry when bound to Fe(II) porphyrins (25)(26)(27)(28). Moreover, high resolution structures of globins complexed with O 2 and NO show very similar binding geometries and local interactions in the heme pocket (29).…”
mentioning
confidence: 81%
“…Of the other two common Fe(II) ligands, CO and NO, NO is the best molecular mimic for O 2 binding. Both O 2 and NO prefer a bent geometry, whereas CO prefers a linear geometry when bound to Fe(II) porphyrins (25)(26)(27)(28). Moreover, high resolution structures of globins complexed with O 2 and NO show very similar binding geometries and local interactions in the heme pocket (29).…”
mentioning
confidence: 81%
“…5,8 Multiple effects from the protein have been identified, including steric hindrance, hydrogen bonding, and local polarity. 1,[13][14][15][16][17] However, due to the large size and the complex structure of protein, the interaction of protein with small molecules becomes extremely complicated. In addition, little attention has been paid to the small side ligands of porphyrin molecule itself.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unsuitability of DFT and MP2 in treating 1 ∆ state of this system, the deviation among their theoretical results is large. By considering the bonding character of the 3 ∑ -state, it should be believed that the results obtained at the CASSCF/6-311+G* level are reliable, and perhaps the B3LYP and MP2 results (58-70 for ω 2 , 40-110 for ω 3 , and 2047-2122 cm -1 for ω 1 ) are fortunately reasonable. These small bending vibrational frequencies and small Si-OC stretching frequencies also imply that there should be similar PES character in the 1 ∆ state to that in the 3 ∑ -state.…”
Section: Linear Sioc Speciesmentioning
confidence: 99%
“…In particular, for the studies on the CO species, much important information has been obtained. A recent survey of the stretching frequencies of CO bonded to the biological molecules has shown that there is an interesting change in the vibrational frequency for CO, 1 the affecting factors resulting in the frequency shift mainly involve the ring-ligand substituents, 2 CO ligand binding geometry and steric effects, [3][4][5] redox potentials, 6 CO binding affinities, 7 and the charge and polar interactions in the protein pocket. 1,8,9 To interpret the dependence of the CO binding on these effect factors, many interesting models have been established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation